EVALUASI PELAKSANAAN PROGRAM ASESMEN NASIONAL (AN) PADA SEKOLAH DASAR SE-GUGUS VII KECAMATAN TAMBUN SELATAN, KABUPATEN BEKASI - Dyah Kartanti; Tita Rosita; Rais Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to evaluate the implementation of the National Assessment (AN) using the Context, Input, Process, and Product (CIPP) model. This descriptive qualitative research was conducted in Cluster VII, South Tambun District, Bekasi Regency. The subjects of the study were school principals, proctors, and technicians. Data collection was carried out through interviews, observations, and documentation. The results of the study indicate that: 1) The context aspect shows that the objectives of the AN have been well understood by the principals. 2) The input aspect shows that facilities and infrastructure are adequate, although some schools face challenges in implementation. 3) The process aspect shows consistency in the implementation of the AN according to the AN Standard Operating Procedures (POS AN). 4) The product aspect shows a need for improvement in the education report card results.